Biosynthesis of sulfur and selenium co-doped ZnO nanoparticles for the enhanced photocatalytic treatment of industrial wastewater - Sulistyo Rini, Ari; Sitorus, Afrida Helena; Rati, Yolanda; Taer, Erman; Usman, Zulkarnain; Jasril; Umar, Akrajas Ali (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
Although ZnO photocatalysts show potential for wastewater treatment, their low efficiency limits the commercialization. To address this problem, we investigated the effect of co-doping ZnO with selenium (4%, fixed) and sulfur (0.5, 1, and 1.5 wt%). The catalysts were synthesized using Matoa leaf extract and zinc nitrate hexahydrate while being subjected to 540 W microwave irradiation. UV-Vis analysis revealed absorption peaks at 340-398 nm with sulfur doping increasing the band gap. XRD confirmed the preservation of the hexagonal wurtzite structure, while FESEM images showed a morphological transformation from nanoflowers to petal flakes with increasing sulfur content. EDX analysis confirmed the presence of S, Se, Zn, and O, while FTIR analysis identified OH groups from the extract in the nanoparticles. BET surface area was found to progressively reduced from 24.58 to 16.86 m²/g with sulfur doping. The co-doped catalyst with 0.5 wt% sulfur (0.5S(4Se-ZnO)) demonstrated the highest degradation of 4-nitrophenol at 99.69%, indicating its applicability in industrial wastewater treatment. These findings indicate that the Se/S co-doped ZnO, prepared via a green synthesis route, holds a strong promise as an efficient and practical photocatalyst for addressing environmental pollution in a sustainable and economical manner.